Thromboembolic events in ß-Thalassemia major patients - Abbas, Sawsan S. (Journal of the Faculty of Medicine Baghdad, 2007)
Background:Seventy eight patients with beta - thalassemia major were Collected randomly from the thalassemia center in Ibn-Al-Baldy Hospital (all of them were transfusion dependent), together with fifty six age and sex matched healthy children were collected as a control. Aim of the study: To determine the incidence of thromboembolism among them and to evaluate the precipitating factors. Patients and Methods: History was taken and physical examination was done . EDTA Anticoagulated blood samples were taken prior to the next transfusion , platelet parameters were estimated for both groups using the MS – 9 coulter counter. Results: Thromboembolic events was detected in five patients (6.41%).The main site was the central nervous system in 4 of them ( 5.2%) followed by the lung ,1 case ( 1.2%). Associated predisposing factors were found in 3 of them (60%).The patients had a statistically significant higher platelet counts, platelet crit, mean platelet volume and platelet distribution width than the control group. The splenectomized had higher platelet counts ,platelet crit than the non splenectomized with nearly equal mean platelet volume and platelet distribution width , a results that is in favour of thrombosis. Conclusions:This results suggest that beta- thalassemia patients had a hypercoagulable state which makes them susceptible to thrombosis and pulmonary embolism even in the young age group and even before splenectomy is performed.